2017
DOI: 10.1093/toxsci/kfx010
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Consequences of Gestational Exposure to Concentrated Ambient Fine and Ultrafine Particles in the Mouse

Abstract: Increasing evidence indicates that the central nervous system (CNS) is a target of air pollution. We previously reported that postnatal exposure of mice to concentrated ambient ultrafine particles (UFP; ≤100 nm) via the University of Rochester HUCAPS system during a critical developmental window of CNS development, equivalent to human 3rd trimester, produced male-predominant neuropathological and behavioral characteristics common to multiple neurodevelopmental disorders, including autism spectrum disorder (ASD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 89 publications
(114 reference statements)
9
78
2
Order By: Relevance
“…33 The few published studies using neuroimaging suggest that pre-natal air pollution exposure affects myelinisation (ie smaller white matter volume, 29 white matter lesions 30 and decrease o pre-frontal cortical thickness 32 ). These results are consistent with the observed effects in mice exposed in utero 14,25 and in elderly human beings, [35][36][37] although cumulative exposure and the mechanisms of action could be different in later life. The studies in mice suggest that the effect of air pollution is principally mediated through chronic stimulation of microglial cells.…”
Section: Vulnerable?supporting
confidence: 91%
See 3 more Smart Citations
“…33 The few published studies using neuroimaging suggest that pre-natal air pollution exposure affects myelinisation (ie smaller white matter volume, 29 white matter lesions 30 and decrease o pre-frontal cortical thickness 32 ). These results are consistent with the observed effects in mice exposed in utero 14,25 and in elderly human beings, [35][36][37] although cumulative exposure and the mechanisms of action could be different in later life. The studies in mice suggest that the effect of air pollution is principally mediated through chronic stimulation of microglial cells.…”
Section: Vulnerable?supporting
confidence: 91%
“…12 Among the various particle types, we found airborne copper to be associated with tissue modifications and functional connectivity in the caudate nucleus in children. 13 Other metals, such as iron, have been linked to structural changes in mice brain, 14 and environmental Fe nanoparticles were found in brain tissue. 15 Furthermore, two recent studies in rats exposed to NO 2 (an urban gas) reported clear evidence of brain damage, 16,17 suggesting a specific neurotoxicity of NO 2 .…”
Section: Pollution?mentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent study showed that exposure of pregnant dams to ultrafine particles (UFP), a component of air pollution, leads to increases in corpus callosum size, hypermyelination and microglial activation in offspring [64]. Similarly, administration of UFP to male and female mouse pups from P4-13 led to a persistent increase in microglia number in males only, as far out as P270 [65].…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%